Translaminar facet joint screw insertion with a rapid prototyping guide template: a cadaver study. Issue 1 (1st January 2019) - Cao, Yuanwu; Zhang, Wenjun; Liang, Yun; Feng, Zhenzhou; Jiang, Chun; Chen, Zixian; Jiang, Xiaoxing
Abstract: It is technically demanding and requires rich experience to insert the translaminar facet screw(TFS) via the paramedian mini-incision approach. It seems that it is easy to place the TFS using computer-assisted design and rapid prototyping(RP) techniques. However, the accuracy and safety of these techniques is still unknown. The aim of this study is to assess the accuracy and safety of translaminar facet screw placement in multilevel unilateral transforaminal lumbar interbody fusion using a rapid prototyping drill guide template system. A patient-matched rapid prototyping translaminar facet screw guide was examined in fourteen cadaveric lumbar spine specimens. A three-dimensional (3D) preoperative screw trajectory was constructed using spinal computed tomography scans, from which individualized guides were developed for the placement of translaminar facet screws. Following bone tunnel establishment, the 3D positioning of the entry point and trajectory of the screws was compared to the preoperative plan as found in the Mimics software.Among 60 trajectories eligible for assessment, no cases of clinically significant laminar perforation were found. The mean deviation between the planned and the actual starting points on spinous process was 1.22 mm. The mean tail and submergence angle deviation was found to be 0.68°and 1.46°, respectively. Among all the deviations, none were found to have any statistical significance. These results indicate that translaminar facet screw placement using the guide system is both accurate and safe.